Strategi Pesantren dalam Membentuk Karakter Kemandirian Santri di Pondok Pesantren Darussa’adah 21 Malang - Eko Yusuf Wahyudi; Muhammad Hasyim; Romadlon Chotib (LPPI Universitas Al-Qolam Malang, 2025)
This research aims to analyze the strategy of the Darussa'adah 21 Sutojayan Pakisaji Malang Islamic Boarding School in forming the independent character of its students. This research uses a qualitative approach with a case study method. Data was collected through interviews, observation and documentation. The results of the research show that the Darussa'adah 21 Sutojayan Pakisaji Malang Islamic Boarding School has several strategies in forming the independent character of its students, namely: getting used to the values ​​of independence, discipline and responsibility. These strategies are implemented through various programs and activities, namely: daily routines, extracurricular activities, student organizations, service to Islamic boarding schools and the community, and alumni empowerment. The conclusion of the research is that the Darussa'adah 21 Sutojayan Pakisaji Malang Islamic Boarding School has successfully implemented various strategies in forming the independent character of its students. These strategies have a positive impact on developing the students' independent character. Key words: character, santri, education, Islam, strategy